1997
DOI: 10.3354/meps148023
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability in recruitment of a temperate, seagrass-associated fish is largely determined by physical processes in the pre- and post-settlement phases

Abstract: Post-settlement King George whiting Sillaginodes punctata were sampled every 3 to 4 d from mid-September to the end of October 1993, at 3 seagrass sites within Port Phillip Bay, Australia. The site closest to the entrance (St Leonards) showed short-lived pulses of recruits in low numbers. The site of intermediate distance into the bay (Grassy Point) showed a similar pattern; however, in this case there was a marked accumulation of recruits over time. In contrast, recruitment was low at the site furthest into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 18 publications
3
92
1
Order By: Relevance
“…For example, S. punctata is a percoid, has a full compliment of fin elements, and falls within a size-range similar to that of reef fishes studied. However, Jenkins & Welsford (2002) found the swimming capabilities of S. punctata post-larvae to be relatively weak, which supports the contention (gained through hydrodynamic dispersal models) that recruitment into Port Phillip Bay is largely a passive process (Jenkins et al 1997(Jenkins et al , 1999.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…For example, S. punctata is a percoid, has a full compliment of fin elements, and falls within a size-range similar to that of reef fishes studied. However, Jenkins & Welsford (2002) found the swimming capabilities of S. punctata post-larvae to be relatively weak, which supports the contention (gained through hydrodynamic dispersal models) that recruitment into Port Phillip Bay is largely a passive process (Jenkins et al 1997(Jenkins et al , 1999.…”
Section: Introductionsupporting
confidence: 56%
“…Early in the recruitment period, most post-larvae are close to the entrance of Port Phillip Bay, but over time numbers decrease in this area and increase in seagrass beds further inside the bay towards the Geelong Arm (Jenkins et al 1996b). At present, hydrodynamic dispersal models and known larval behaviours have failed to explain the settlement of S. punctata to seagrass beds located in the Geelong Arm on the western side of Port Phillip Bay (Jenkins et al 1997(Jenkins et al , 1999. The aim of this study, using cage inclusion experiments, was to assess whether wave disturbance generated by onshore winds can facilitate secondary dispersal in S. punctata post-larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Port Phillip Bay (Victoria, Australia), postlarval abundances of King George whiting (Sillaginodes punctata) at seagrass sites are strongly correlated with zonal westerly winds, the main westerly wind belt over Tasmania, and are likely to be influenced by climate change (Jenkins et al 1997;Jenkins 2005).…”
Section: Ocean Currents and Wind Patternsmentioning
confidence: 99%
“…Sea-level rise in Australia may also directly affect estuarine and marine fish during their pre-and post-settlement phases. For example, Jenkins et al (1997) showed that spatial and temporal variability in recruitment of a temperate, seagrass-associated fish, King George whiting (Sillaginodes punctata), was largely determined by physical processes, including the residual sea level (caused by changes in barometric pressure). Other Australian commercial species that might be similarly affected include pink snapper (Pagurus auratus), southern sea garfish (Hyporhamphus melanochir), Australian herring (Arripis georgianus), whiting and mullet (Fletcher and Head 2006).…”
Section: Sea-level Risementioning
confidence: 99%